A Cu-V metal organic hybrid crystalline material and its preparation method and application

The Cu-V metal organic hybrid crystalline material was constructed through diffusion synthesis method, which solved the problems of poor stability and large amount of existing catalysts, and achieved efficient and stable sulfoxide synthesis effect.

CN119140161BInactive Publication Date: 2025-03-04ZHEJIANG UNIV +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411024480.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-29
Publication Date
2025-03-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing transition metal catalysts have problems such as poor stability, large amount of use and metal residue in the sulfoxide synthesis process of sulfoxide, which limits their large-scale application.

Method used

Through the diffusion synthesis method, vanadium and copper metals are combined with the organic ligand 4,4'-bipyridine to construct Cu-V metal organic hybrid crystalline material to improve the stability and activity of the catalytic material.

Benefits of technology

High stability and high activity of the catalyst are achieved, the amount of catalyst is used is reduced, and the production efficiency of sulfoxide compounds is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119140161B_ABST
    Figure CN119140161B_ABST
Patent Text Reader

Abstract

The invention discloses a Cu-V metal organic hybrid crystalline material and a preparation method and application thereof. The chemical formula of the Cu-V metal organic hybrid crystalline material is H[Cu(bpy)VO4(H2O)3], wherein bpy represents 4,4'-bipyridine. The invention successfully combines hetero-ammonium metavanadate, copper sulfate and 4,4'-bipyridine by a diffusion method to construct a Cu-V metal organic hybrid crystalline material with high stability, high activity and low dosage, which shows great potential application value in the preparation of sulfoxides.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts, and specifically relates to a Cu-V metal organic hybrid crystalline material and a preparation method and application thereof. Background Art

[0002] Sulfoxide compounds have a wide range of biological activities and are widely used as antibacterial agents, insecticides and anti-tumor drugs in the fields of pesticides and medicine. In addition, the acidic gas or liquid produced by the combustion of sulfides in fuel oil will corrode the machinery and pollute the atmosphere, and desulfurization treatment is required before use. The method of exploring new catalysts to catalyze the oxidation of sulfide to synthesize sulfoxides has been continuously reported. Among them, the use of transition metal catalysis (CN111153837B) to convert these sulfides into sulfoxide compounds is one of its important preparation methods, which not only provides an effective way for the synthesis of sulfoxide compounds, but also provides a new idea for the desulfurization treatment of fuel oil.

[0003] The method of converting sulfides into sulfoxides by catalytic oxidation with cheap transition metals can not only significantly reduce the production cost of sulfoxides, but also achieve the desulfurization of fuel at a low cost, which is of great significance. Therefore, this method has always attracted the attention of materials and organic chemists. However, this type of method still has some defects, such as poor stability of metal catalysts, large dosage, and metal residues, which limit its large-scale application.

[0004] Metal-organic hybrid materials are multiphase materials coordinated by organic ligands and inorganic metal ions. The combination of the two not only has the advantages of both, but also overcomes the problems of poor stability, large dosage, and metal residue of metal catalysts. Therefore, it is of great research significance to develop a new method for catalyzing the oxidation of sulfide to prepare sulfoxide compounds using transition metal-organic hybrid materials with high efficiency, low cost, and good stability. Summary of the invention

[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0006] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0007] One of the purposes of the present invention is to provide a Cu-V metal organic hybrid crystalline material, to construct a Cu-V metal organic hybrid crystalline material with high stability and high activity, which shows great potential application value in the preparation of sulfoxides.

[0008] In order to solve the above technical problems, the present invention provides the following technical solutions: a Cu-V metal organic hybrid crystalline material, wherein the chemical formula of the Cu-V metal organic hybrid crystalline material is H[Cu(bpy)VO4(H2O)3], wherein bpy represents 4,4'-bipyridine; the molecular formula is C 10 H 15 N2VO7Cu, molecular weight is 389.72; crystal system is hexagonal; space group is P6(5); unit cell parameters are α=90, β=90, γ=120, Z=2.

[0009] Another object of the present invention is to provide a method for preparing the Cu-V metal organic hybrid crystalline material as described above, comprising:

[0010] Mix and dissolve the vanadium salt and the copper salt in deionized water, and adjust the pH value to 3-4 to obtain a reaction solution A;

[0011] Dissolving 4,4'-bipyridine in acetonitrile to obtain reaction solution B;

[0012] The reaction liquid A is added to the bottom of the reaction container as the lower layer, and then a mixed solution of acetonitrile and deionized water is added as the middle layer. Finally, the reaction liquid B is added as the upper layer, and slowly diffused at room temperature to obtain a Cu-V metal organic hybrid crystalline material.

[0013] As a preferred embodiment of the method for preparing the Cu-V metal organic hybrid crystalline material of the present invention, the molar ratio of the vanadium salt to the copper salt is 1:1-3.

[0014] As a preferred embodiment of the method for preparing the Cu-V metal organic hybrid crystalline material of the present invention, the molar ratio of the vanadium salt to 4,4'-bipyridine is 1:2-4.

[0015] As a preferred embodiment of the method for preparing the Cu-V metal organic hybrid crystalline material of the present invention, the vanadium salt comprises one of ammonium metavanadate and sodium metavanadate.

[0016] As a preferred embodiment of the method for preparing the Cu-V metal-organic hybrid crystalline material of the present invention, the copper salt comprises one of copper sulfate, copper nitrate and copper chloride.

[0017] As a preferred solution of the method for preparing the Cu-V metal-organic hybrid crystalline material of the present invention, wherein: the slow diffusion at room temperature has a reaction time of 7 days.

[0018] Another object of the present invention is to provide the use of the Cu-V metal organic hybrid crystalline material as described above in catalyzing the synthesis of benzyl sulfoxide from anisyl thioether, comprising:

[0019] The Cu-V metal organic hybrid crystalline material is subjected to oxidation reaction with anisyl thioether and tert-butyl peroxide at a certain temperature to obtain benzyl sulfoxide.

[0020] As a preferred embodiment of the application of the Cu-V metal organic hybrid crystalline material in the catalysis of thioanisole to synthesize benzyl sulfoxide, the molar ratio of the Cu-V metal organic hybrid crystalline material to thioanisole is 1:20-100.

[0021] As a preferred solution for the application of the Cu-V metal organic hybrid crystalline material of the present invention in catalyzing the synthesis of benzyl sulfoxide from anisyl thioether, the reaction temperature is 40 to 80° C. and the reaction time is 2 to 4 hours.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] The present invention combines vanadium and copper metals with an organic ligand 4,4'-bipyridine by a diffusion synthesis method to construct a Cu-V metal organic hybrid crystalline material, which can not only improve the stability of the catalytic material, but also improve its catalytic activity. Therefore, it is of great significance to construct a Cu-V metal organic hybrid crystalline material with high stability and high activity to prepare sulfoxide compounds. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0025] Figure 1 This is a coordination diagram of the Cu-V metal-organic hybrid crystalline material prepared in Example 1 of the present invention, wherein 1 represents Cu; 2 represents C; 3 represents N; 4 represents O; and 5 represents V.

[0026] Figure 2 This is a schematic diagram of the three-dimensional structure of the Cu-V metal-organic hybrid crystalline material prepared in Example 1 of the present invention.

[0027] Figure 3 This is an infrared graph of the Cu-V metal-organic hybrid crystalline material prepared in Example 1 of the present invention.

[0028] Figure 4 This is the PXRD pattern of the Cu-V metal-organic hybrid crystalline material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0029] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0030] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0031] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0032] The single crystal diffractometer used in the present invention is an ApexII single crystal diffractometer produced by Bruker Corporation.

[0033] Unless otherwise specified, the chemical reagents used in the examples of the present invention are all commercially available analytically pure.

[0034] Example 1

[0035] This embodiment provides a method for preparing a Cu-V metal-organic hybrid crystalline material, specifically:

[0036] (1) ammonium metavanadate (0.02 mmol) and copper sulfate (0.03 mmol) were dissolved in deionized water (5 mL), and the pH value of the reaction solution was adjusted to 3 using 1 mol / L NaOH solution and 1 mol / L HNO3 solution to obtain reaction solution A; 4,4'-bipyridine (0.04 mmol) was dissolved in acetonitrile (5 mL) to obtain reaction solution B;

[0037] (2) Reaction solution A was added to the bottom of the test tube as the lower layer, and then a mixed solution of acetonitrile and deionized water (volume ratio 1:1, 2 mL) was added as the middle layer, and finally reaction solution B was added as the upper layer. The mixture was slowly diffused at room temperature for 7 days to obtain blue block crystals, namely, Cu-V metal organic hybrid crystalline materials, with a yield of 65% (based on 4,4'-bipyridine).

[0038] The structure of the metal-organic hybrid material containing heteropolyacid prepared in Example 1 was determined using a Bruker Apex IICCD diffractometer. The determination object was a minimum structural repeating unit. The determination result was consistent with its theoretical model. The specific crystal structure determination data are shown in Table 1.

[0039] Table 1

[0040]

[0041]

[0042] As shown in Table 1, X-ray single crystal diffraction analysis shows that the molecular formula of the metal organic hybrid material containing heteropoly acid prepared in Example 1 is C 10 H 15 N2VO7Cu.

[0043] Figure 1 This is a schematic diagram of the coordination of the Cu-V metal-organic hybrid crystalline material prepared in Example 1 of the present invention. Figure 2 A schematic diagram of the three-dimensional structure of the Cu-V metal-organic hybrid crystalline material prepared in Example 1 of the present invention;

[0044] Figure 3 This is an infrared curve of the Cu-V metal organic hybrid crystalline material prepared in Example 1 of the present invention; Figure 4 This is the PXRD pattern of the Cu-V metal-organic hybrid crystalline material prepared in Example 1 of the present invention, 1 is the simulated peak position, 2 is the experimental peak position, and it can be seen that the experimental peak position and the simulated peak position of the compound in the PXRD spectrum are basically consistent, indicating that the Cu-V metal-organic hybrid crystalline material prepared in Example 1 has good purity.

[0045] Example 2

[0046] The difference between Example 2 and Example 1 is that the ratio and pH of the raw materials are changed, specifically:

[0047] (1) ammonium metavanadate (0.02 mmol) and copper sulfate (0.04 mmol) were dissolved in deionized water (5 mL), and the pH value of the reaction solution was adjusted to 4 using 1 mol / L NaOH solution and 1 mol / L HNO3 solution to obtain reaction solution A; 4,4'-bipyridine (0.06 mmol) was dissolved in acetonitrile (5 mL) to obtain reaction solution B;

[0048] (2) Reaction solution A was added to the bottom of the test tube as the lower layer, and then a mixed solution of acetonitrile and deionized water (volume ratio 1:1, 2 mL) was added as the middle layer, and finally reaction solution B was added as the upper layer. The mixture was slowly diffused at room temperature for 7 days to obtain blue block crystals, namely, Cu-V metal organic hybrid crystalline materials, with a yield of 53% (based on 4,4'-bipyridine).

[0049] Example 3

[0050] The difference between Example 3 and Example 1 is that the type of vanadium salt is changed, specifically:

[0051] (1) Sodium metavanadate (0.02 mmol) and copper sulfate (0.03 mmol) were dissolved in deionized water (5 mL), and the pH value of the reaction solution was adjusted to 3 using 1 mol / L NaOH solution and 1 mol / L HNO3 solution to obtain reaction solution A; 4,4'-bipyridine (0.04 mmol) was dissolved in acetonitrile (5 mL) to obtain reaction solution B;

[0052] (2) Reaction solution A was added to the bottom of the test tube as the lower layer, and then a mixed solution of acetonitrile and deionized water (volume ratio 1:1, 2 mL) was added as the middle layer, and finally reaction solution B was added as the upper layer. The mixture was slowly diffused at room temperature for 7 days to obtain blue block crystals, namely, Cu-V metal organic hybrid crystalline materials, with a yield of 47% (based on 4,4'-bipyridine).

[0053] Example 4

[0054] The difference between Example 4 and Example 1 is that the type of copper salt is changed, specifically:

[0055] (1) Sodium metavanadate (0.02 mmol) and copper nitrate (0.03 mmol) were dissolved in deionized water (5 mL), and the pH value of the reaction solution was adjusted to 3 using 1 mol / L NaOH solution and 1 mol / L HNO3 solution to obtain reaction solution A; 4,4'-bipyridine (0.04 mmol) was dissolved in acetonitrile (5 mL) to obtain reaction solution B;

[0056] (2) Reaction solution A was added to the bottom of the test tube as the lower layer, and then a mixed solution of acetonitrile and deionized water (volume ratio 1:1, 2 mL) was added as the middle layer, and finally reaction solution B was added as the upper layer. The mixture was slowly diffused at room temperature for 7 days to obtain blue block crystals, namely, Cu-V metal organic hybrid crystalline materials, with a yield of 44% (based on 4,4'-bipyridine).

[0057] Example 5

[0058] The difference between Example 5 and Example 1 is that the type of copper salt is changed, specifically:

[0059] (1) Sodium metavanadate (0.02 mmol) and copper chloride (0.03 mmol) were dissolved in deionized water (5 mL), and the pH value of the reaction solution was adjusted to 3 using 1 mol / L NaOH solution and 1 mol / L HNO3 solution to obtain reaction solution A; 4,4'-bipyridine (0.04 mmol) was dissolved in acetonitrile (5 mL) to obtain reaction solution B;

[0060] (2) Reaction solution A was added to the bottom of the test tube as the lower layer, and then a mixed solution of acetonitrile and deionized water (volume ratio 1:1, 2 mL) was added as the middle layer, and finally reaction solution B was added as the upper layer. The mixture was slowly diffused at room temperature for 7 days to obtain blue block crystals, namely, Cu-V metal organic hybrid crystalline materials, with a yield of 49% (based on 4,4'-bipyridine).

[0061] It can be seen from Examples 1 and 3 to 5 that, under the same conditions, ammonium metavanadate and copper sulfate have better activity, which promotes the efficiency and selectivity of the reaction with 4,4'-bipyridine, ultimately leading to an increase in yield. Under the conditions of Example 1, the yield of the Cu-V metal organic hybrid crystalline material is the highest, reaching 65%.

[0062] Comparative Example 1

[0063] Comparative Example 1 is based on Example 1, except that the copper salt is replaced by zinc sulfate or iron sulfate, and the rest of the preparation method is consistent with Example 1; the obtained product is an amorphous powder, and a crystalline sample suitable for X-ray single crystal analysis cannot be obtained.

[0064] Comparative Example 2

[0065] Comparative Example 2 is based on Example 1, except that 4,4'-bipyridine is replaced by pyridine or imidazole, and the rest of the preparation method is consistent with Example 1; the obtained product is an amorphous powder, and a crystalline sample suitable for X-ray single crystal analysis cannot be obtained.

[0066] Example 6

[0067] This embodiment provides a method for preparing benzyl sulfoxide, specifically:

[0068] The Cu-V metal organic hybrid crystalline material (40 μmol) prepared in Example 1, TBHP (1.25 mmol), thioanisole (1 mmol) and methanol (3 mL) were added into a 15 mL reaction tube in sequence, and reacted at 60° C. for 3 h to obtain benzyl sulfoxide with a yield of 98%. The reaction equation is:

[0069]

[0070] The yield was calculated as follows: yield = (amount of benzyl sulfoxide substance / amount of thioanisole substance before the reaction) × 100%.

[0071] Example 7

[0072] The difference between this embodiment and embodiment 6 is that the reaction temperature and time are adjusted, specifically:

[0073] The Cu-V metal organic hybrid crystalline material (40 μmoL) prepared in Example 1, TBHP (1.25 mmol), anisyl thioether (1 mmol) and methanol (3 mL) were added into a 15 mL reaction tube in sequence and reacted at 70° C. for 2 h to obtain benzyl sulfoxide with a yield of 97%.

[0074] Example 8

[0075] The difference between this embodiment and embodiment 6 is that the amount of the catalyst is adjusted, specifically:

[0076] The Cu-V metal organic hybrid crystalline material (20 μmoL) prepared in Example 1, TBHP (1.25 mmol), anisyl thioether (1 mmol) and methanol (3 mL) were added into a 15 mL reaction tube in sequence and reacted at 60° C. for 3 h to obtain benzyl sulfoxide with a yield of 98%.

[0077] The present invention combines vanadium and copper metals with an organic ligand 4,4'-bipyridine through a diffusion synthesis method to construct a Cu-V metal organic hybrid crystalline material, which improves the catalyst activity and stability, and greatly reduces the amount of catalyst used. The Cu-V metal organic hybrid crystalline material exhibits high catalytic activity and stability in catalyzing the oxidation of sulfides to synthesize sulfoxides.

[0078] The invention discloses a Cu-V metal organic hybrid crystalline material with high catalytic activity, good thermal stability, low dosage, and convenient operation of the synthesis method. The invention uses a diffusion synthesis method to successfully synthesize a Cu-V metal organic hybrid crystalline material using ammonium metavanadate, copper sulfate and 4,4'-bipyridine, and the material shows great potential application value in the conversion of sulfide into sulfoxide.

[0079] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.

Claims

1. A Cu-V metal organic hybrid crystalline material, characterized in that: The chemical formula of the Cu-V metal organic hybrid crystalline material is H[Cu(bpy)VO4(H2O)3], wherein bpy represents 4,4'-bipyridine; the molecular formula is C 10 H 15 N2VO7Cu, molecular weight 389.72; crystal system is hexagonal; space group is P6(5); unit cell parameters are a= 11.202(5)Å, b= 11.202(5)Å, c= 21.593(5)Å, V = 2346.576Å 3 , α=90°, β=90°, γ=120°, Z =2.

2. The method for preparing the Cu-V metal organic hybrid crystalline material according to claim 1, characterized in that: include, Mix and dissolve the vanadium salt and the copper salt in deionized water, and adjust the pH value to 3-4 to obtain a reaction solution A; Dissolving 4,4'-bipyridine in acetonitrile to obtain reaction solution B; The reaction liquid A is added to the bottom of the reaction container as the lower layer, and then a mixed solution of acetonitrile and deionized water is added as the middle layer. Finally, the reaction liquid B is added as the upper layer, and slowly diffused at room temperature to obtain a Cu-V metal organic hybrid crystalline material.

3. The method for preparing the Cu-V metal organic hybrid crystalline material according to claim 2, characterized in that: The molar ratio of the vanadium salt to the copper salt is 1:1-3.

4. The method for preparing the Cu-V metal organic hybrid crystalline material according to claim 2, characterized in that: The molar ratio of the vanadium salt to 4,4'-bipyridine is 1:2-4.

5. The method for preparing the Cu-V metal organic hybrid crystalline material according to claim 4, characterized in that: The vanadium salt includes one of ammonium metavanadate and sodium metavanadate.

6. The method for preparing the Cu-V metal organic hybrid crystalline material according to claim 2 or 3, characterized in that: The copper salt includes one of copper sulfate, copper nitrate and copper chloride.

7. The method for preparing the Cu-V metal organic hybrid crystalline material according to any one of claims 2, 3 and 5, characterized in that: The reaction was slow diffused at room temperature and lasted for 7 days.

8. The use of the Cu-V metal organic hybrid crystalline material as claimed in claim 1 in catalyzing the synthesis of benzyl sulfoxide from anisyl thioether, characterized in that: include, The Cu-V metal organic hybrid crystalline material is subjected to oxidation reaction with anisyl thioether and tert-butyl peroxide at a certain temperature to obtain benzyl sulfoxide.

9. The use according to claim 8, characterized in that: The molar ratio of the Cu-V metal organic hybrid crystalline material to thioanisole is 1:20-100.

10. The use according to claim 8 or 9, characterized in that: The reaction temperature is 40-80° C., and the reaction time is 2-4 hours.

Citation Information

Patent Citations

  • A method for preparing sulfoxide compounds by catalytic oxidation of sulfide with nickel compounds

    CN111153837B

  • Polyoxometalates material with manganese and copper as hetero atoms using isoplyacid precursor to assemble

    CN109956981A

  • Metal chelator compounds, coordination complexes, and methods of preparation and use thereof

    WO2024044271A2